2005
DOI: 10.1128/jcm.43.2.945-947.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Bartonella vinsonii subsp. arupensis as an Agent of Blood Culture-Negative Endocarditis in a Human

Abstract: We report the case of a patient hospitalized with endocarditis. The etiological diagnosis of Bartonella was suggested by detection of high titers of antibodies by immunofluorescence and Western blotting. Two different nested PCRs performed on sera identified Bartonella vinsonii subsp. arupensis by sequencing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 11 publications
0
27
0
1
Order By: Relevance
“…During the study period, we diagnosed 106 cases of Bartonella endocarditis, 47 of which have been mentioned or reported (11,(13)(14)(15)19). Serum, EDTA blood, and valvular specimens were available for 102, 60, and 52 of these patients, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the study period, we diagnosed 106 cases of Bartonella endocarditis, 47 of which have been mentioned or reported (11,(13)(14)(15)19). Serum, EDTA blood, and valvular specimens were available for 102, 60, and 52 of these patients, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…berkhoffii (9,10), B. vinsonii subsp. arupensis (11), Bartonella koehlerae (12), Bartonella alsatica (13,14), and "Candidatus Bartonella mayotimonensis" (15), have occasionally been reported in the literature. Epidemiological data suggest a European-African gradient distribution in the prevalence of Bartonella endocarditis, the highest prevalence being reported in southern countries (7).…”
mentioning
confidence: 99%
“…uring the past decade, the number of Bartonella species that are documented human pathogens has rapidly increased (1 (1)(2)(3)(4)(5)(6)(7). Sheep are the most likely reservoir hosts for Candidatus B. melophagi and sheep keds may be a vector for their transmission among sheep.…”
mentioning
confidence: 99%
“…14 Ninety-five percent of Bartonella endocarditis is caused by either B. quintana or B. henselae . 2,14 However, other Bartonella species including B. koehlerae , 18 B. alsatica , 19,20 B. elizabethae , 21 and B. vinsonii 2224 have also been reported as causing culture-negative endocarditis in humans. 25 Epidemiology studies have identified exposure to cats and preexisting valvular disease as risk factors for development of B. henselae endocarditis; homelessness, alcohol abuse, and prior louse infections are known risk factors for B. quintana endocarditis.…”
Section: Discussionmentioning
confidence: 99%